Maternal correlates of maternal child feeding practices: a systematic review. Issue 1 (13th September 2012) - McPhie, Skye; Skouteris, Helen; Daniels, Lynne; Jansen, Elena
Abstract: Establishing healthy eating habits early in life is one important strategy to combat childhood obesity. Given that early maternal child feeding practices have been linked to child food intake and weight, identifying the maternal correlates of maternal child feeding practices is important in order to understand the determinants of childhood obesity; this was the overall aim of the current review. Academic databases were searched for studies examining the relationship between maternal child feeding practices and parenting, personal characteristics and psychopathology of mothers with preschoolers. Papers were limited to those published in English, between January 2000 and June 2012. Only studies with mothers of normally developing children between the ages of 2 and 6 years were included. There were no restrictions regarding the inclusion of maternal nationality or socioeconomic status (SES). Seventeen eligible studies were sourced. Information on the aim, sample, measures and findings of these was summarised into tables. The findings of this review support a relationship between maternal controlling parenting, general and eating psychopathology, and SES and maternal child feeding practices. The main methodological issues of the studies reviewed included inconsistency in measures of maternal variables across studies and cross‐sectional designs. We conclude that the maternal correlates associated with maternal child feeding practices are complex, and the pathways by which maternal correlates impact these feeding practices require further investigation.